Effects of personalized nursing on treatment adherence and clinical symptoms in prostatitis patients - Zhu, Yueting (Frontiers in Medicine, 2025)
BackgroundChronic prostatitis is a common urological condition, often presenting with urinary irritation and chronic pelvic pain. These symptoms can negatively affect patients’ daily life and treatment adherence, with some showing poor cooperation during therapy. Therefore, appropriate nursing guidance is essential to ensure treatment efficacy and support self-management.ObjectiveThis study aimed to evaluate the impact of personalized nursing on treatment adherence and clinical symptoms in patients with prostatitis.MethodsEighty-five prostatitis patients were enrolled and randomly separated into two groups. The control group (n = 47) adopted conventional nursing mode; the observation group (n = 38) adopted personalized nursing mode on top of the control group. Before and after nursing, the clinical symptoms were assessed by the National Institutes of Health-Chronic Prostatitis Symptom Index (NIH-CPSI); the psychological status was evaluated by the Self-rating Anxiety Scale (SAS) and the Self-rating Depression Scale (SDS). The maximum and average urine flow rate, the treatment adherence, and the health behavior competence, including health responsibility, nutrition, exercise, and psychological well-being were compared. Prostate fluid specimens were collected and the levels of tumor necrosis factor-α (TNF-α), prostaglandin E2 (PGE2) and cyclooxygenase-2 (COX-2) were measured by radioimmunoassay.ResultsFollowing nursing intervention, both groups showed improvements across clinical and biochemical parameters. NIH-CPSI, SAS, and SDS scores declined significantly, while maximum and average urinary flow rates increased. Treatment adherence and health behavior competence were also enhanced in both groups. Notably, the observation group demonstrated greater improvements in all these outcomes, with lower symptom and psychological scores, higher urinary flow rates, better adherence and self-management, as well as more pronounced reductions in TNF-α, PGE2, and COX-2 levels compared with the control group.ConclusionPersonalized nursing improves treatment adherence, health behaviors, and quality of life in patients with prostatitis.